Inhibition of p38 MAPK Signaling Augments Skin Tumorigenesis via NOX2 Driven ROS Generation - Liu, Liang; Rezvani, Hamid Reza; Back, Jung Ho; Hosseini, Mohsen; Tang, Xiuwei; Zhu, Yucui; Mahfouf, Walid; Raad, Houssam; Raji, Grace; Athar, Mohammad; Kim, Arianna L.; Bickers, David R. (PLOS ONE, 2014)
p38 mitogen-activated protein kinases (MAPKs) respond to a wide range of extracellular stimuli. While the inhibition of p38 signaling is implicated in the impaired capacity to repair ultraviolet (UV)-induced DNA damage—a primary risk factor for human skin cancers—its mechanism of action in skin carcinogenesis remains unclear, as both anti-proliferative and survival functions have been previously described. In this study, we utilized cultured keratinocytes, murine tumorigenesis models, and human cutaneous squamous cell carcinoma (SCC) specimens to assess the effect of p38 in this regard. UV irradiation of normal human keratinocytes increased the expression of all four p38 isoforms (α/β/γ/δ); whereas irradiation of p53-deficient A431 keratinocytes derived from a human SCC selectively decreased p38α, without affecting other isoforms. p38α levels are decreased in the majority of human cutaneous SCCs assessed by tissue microarray, suggesting a tumor-suppressive effect of p38α in SCC pathogenesis. Genetic and pharmacological inhibition of p38α and in A431 cells increased cell proliferation, which was in turn associated with increases in NAPDH oxidase (NOX2) activity as well as intracellular reactive oxygen species (ROS). These changes led to enhanced invasiveness of A431 cells as assessed by the matrigel invasion assay. Chronic treatment of p53-/-/SKH-1 mice with the p38 inhibitor SB203580 accelerated UV-induced SCC carcinogenesis and increased the expression of NOX2. NOX2 knockdown suppressed the augmented growth of A431 xenografts treated with SB203580. These findings indicate that in the absence of p53, p38α deficiency drives SCC growth and progression that is associated with enhanced NOX2 expression and ROS formation.